The relative roles of upper and lower tropospheric thermal contrasts and tropical influences in driving Asian summer monsoons. Issue 13 (9th July 2013) - Dai, Aiguo; Li, Hongmei; Sun, Ying; Hong, Li‐Ciao; Ho, Lin; Chou, Chia; Zhou, Tianjun
Abstract: [1] Summer thermal structure and winds over Asia show a larger land‐ocean thermal gradient in the upper than in the lower troposphere, implying a bigger role of the upper troposphere in driving the Asian summer monsoon circulation. Using data from atmospheric re‐analyses and model simulations, we show that the land‐ocean thermal contrast in the mid‐upper (200–500 hPa) troposphere (TCupper) contributes about three times as much as the thermal contrast in the mid‐lower (500–850 hPa) troposphere (TClower) in determining both the strength and variations of Asian summer monsoon circulations. Tropical sea surface temperature anomalies associated with the annual cycle, El Niño‐Southern Oscillation, decadal changes, and global warming all are accompanied with much larger variations and changes in TCupper than in TClower, partly due to enhanced latent heating aloft from convection. The variations and changes in TCupper and TClower are highly correlated with the strength of the South Asian Summer Monsoon (SASM) and the East Asian Summer Monsoon (EASM) in their respective sectors during the past 50–60 years. In particular, the weakening of the EASM since the 1950s is caused by the weakening mainly in TCupper and secondarily in TClower induced mainly by recent tropical surface warming, although spurious cooling over East Asia seen in reanalysis data may have enhanced this weakening. However, the strength of the SASM and EASM monsoons follows TCupper but decouples with TClower in the global warming case in the 21 st century. The results suggest that the TCupper plays a dominant role and provides an efficient mechanism through which tropical oceans can influence extratropical monsoons. Key Points: The land‐sea T gradient is more important in the upper than in lower troposphere Tropical oceans influence extra‐tropical monsoons through the upper troposphere Monsoon response to global warming depends on tropospheric warming patterns